Water consumption analysis across the life cycle of beef: Environmental impacts and mitigation strategies - Johannes, Hendro Putra; Akbar, Muhammad Rahmat (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Demand for beef is predicted to be risen by 74%, followed by the explosion of the global population by 9.7 billion in 2050. Australia as the most significant exporter of beef, together with America as the leading market, contribute vital roles. The increase in demand causes environmental impacts such as water scarcity. Methods: This study used a systematic literature review method to collect and disseminate relevant evidence from scientific sources related to air consumption in the beef and plant-based product supply chain. The process involved five main steps: problem formulation, data collection, data evaluation, evidence deduction, and interpretation of results. Findings: Based on the life cycle perspective, a kilogram of meat consumption from beef exported to America is 441.8–597.6 liters. The consumption includes processes such as nursery, fattening, cutting, transportation to Australian port, departure to America, and distribution within America. Conclusion: For instance, industrialization will reduce the water consumption, however, causes other environmental impacts. Therefore, dietary changes to vegetarianism combined with organic system becomes the best solution offered. Novelty/Originality of This Study: The novelty of this study lies in the life cycle analysis of water consumption in Australian beef exports to the US and highlights the trade-off between industrial efficiency and environmental sustainability while proposing dietary changes as a potential mitigation strategy.